Pendidikan Islam di Negara Turki - Barkatillah (Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study is to describe and analyze Islamic Education in Turkey from the aspects of the curriculum, the education system. This research method is a qualitative research with a literature review method approach. Sources of data used in research include Islamic Education books, research journals, and supporting websites. The results of the research are that the latest government policy is to make compulsory education, which was originally eight years, into twelve years divided into three levels, namely elementary school level, middle school level and high school level.